BANKING INVESTMENT ACTIVITY AND REGIONAL INDUSTRIAL DEVELOPMENT: EVIDENCE FROM HAMKORBANK ATB TERMIZ BRANCH, UZBEKISTAN - Qulsoatov Jushqin; O.Mirzayev (TADQIQOTLAR, 2026)
Annotation. This study examines the relationship between banking investment activity  and  regional  industrial  development,  focusing  on  the  experience  of Hamkorbank ATB Termiz Branch in Uzbekistan. The research analyzes the role of bank investments in supporting industrial enterprises, stimulating production growth, and  enhancing  regional  economic  performance.  Special  attention  is  given  to  the financing  mechanisms  employed  by  the  bank  and  their  impact  on  industrial modernization and business expansion.